Glycolytic Dependency of High-Level Nitric Oxide Resistance and Virulence in Staphylococcus aureus - Nicholas P. Vitko (American Society for Microbiology, 2015)
ABSTRACT Staphylococcus aureus is a prolific human pathogen capable of causing severe invasive disease with a myriad of presentations. The ability of S. aureus to cause infection is strongly linked with its capacity to overcome the effects of innate immunity, whether by directly killing immune cells or expressing factors that diminish the impact of immune effectors. One such scenario is the induction of lactic acid fermentation by S. aureus in response to host nitric oxide (NO·). This fermentative activity allows S. aureus to balance redox during NO·-induced respiration inhibition. However, little is known about the metabolic substrates and pathways that support this activity. Here, we identify glycolytic hexose catabolism as being essential for S. aureus growth in the presence of high levels of NO·. We determine that glycolysis supports S. aureus NO· resistance by allowing for ATP and precursor metabolite production in a redox-balanced and respiration-independent manner. We further demonstrate that glycolysis is required for NO· resistance during phagocytosis and that increased levels of extracellular glucose limit the effectiveness of phagocytic killing by enhancing NO· resistance. Finally, we demonstrate that S. aureus glycolysis is essential for virulence in both sepsis and skin/soft tissue models of infection in a time frame consistent with the induction of innate immunity and host NO· production. IMPORTANCE Staphylococcus aureus is a leading human bacterial pathogen capable of causing a wide variety of diseases that, as a result of antibiotic resistance, are very difficult to treat. The frequency of S. aureus tissue invasion suggests that this bacterium has evolved to resist innate immunity and grow using the nutrients present in otherwise sterile host tissue. We have identified glycolysis as an essential component of S. aureus virulence and attribute its importance to promoting nitric oxide resistance and growth under low oxygen conditions. Our data suggest that diabetics, a patient population characterized by excess serum glucose, may be more susceptible to S. aureus as a result of increased glucose availability. Furthermore, the essential nature of S. aureus glycolysis indicates that a newly developed glycolysis inhibitor may be a highly effective treatment for S. aureus infections.